Civilian oversight of police. A test of capture theory - Prenzler, Tim (The British journal of criminology, 2000)
Many jurisdictions have created external oversight bodies for police following problems of recurring misconduct and the failure of internal control mechanisms. Questions inevitably follow about the effectiveness of the new bodies to detect and prevent abuses of power. One potential source of ineffectiveness is undue influence or capture' by police. This paper reviews developments in external oversight internationally and examines the issue of capture in detail using an Australian case study of the Queensland Police Service and the Queensland Criminal Justice Commission (CJC). The question of capture was assessed by analysing reports on significant issues involving the CJC and police. Cases of zealous enforcement of rules were apparent, but the study identified a generally weak approach on the part of the Commission to enforcement and direction. Crucial elements of the CJC's structure and functions have exposed it to capture; including a role in facilitating police management, joint operations against organized crime, and reliance on seconded police investigators. The available evidence did not confirm a case of direct capture, but there was evidence from audits of investigations that police involvement in investigations and discipline contributed to a marked attrition of complaints. Weakness in oversight could also be related to the combined effects of an appeasement strategy, an overly legalistic organizational culture, and inadequate quality control. Practical measures are recommended to improve accountability that have general application to police oversight bodies. These include a clearer separation between police and the regulator, quality assessment measures, and exclusion of a facilitation role to allow the regulator to focus on police conduct